Teaching Health-Care Providers to Query Patients With Cancer About Sexual and Gender Minority (SGM) Status and Sexual Health. (June 2019) - Cathcart-Rake, Elizabeth J.; Breitkopf, Carmen Radecki; Kaur, Judith; O'Connor, Jennifer; Ridgeway, Jennifer L.; Jatoi, Aminah
End of life is difficult for all patients but sexual and gender minorities (SGM) are prone to isolation and loneliness, especially if their SGM status is unknown or unaccepted. In oncology clinics, where goals of care discussions about end of life are integral and frequent, querying patients about their SGM status and sexual health is of particular importance. The American Society of Clinical Oncology recently released a position statement that called for greater focus on SGM populations with the goal of reducing and eventually eliminating disparities in cancer care within this group. An important first step in addressing such disparities is learning how best to train cancer health-care providers to ask patients about their SGM status and about sexual health in general. This article summarizes the mandate for understanding cancer issues in SGM populations and the dearth of cancer-related data within this group. This article also describes an ongoing 3-part study intended to build a mini curriculum with the goal of helping cancer health-care providers to ask patients with cancer about SGM status and to ask all patients with cancer about sexual health issues. The results of this ongoing study could potentially improve end-of-life care for subgroups of patients.